Fangirl. 2 - Maggs, Sam; Rowell, Rainbow (Viz Media, LLC, 2022)
"Cath is a Simon Snow fan. Okay, everybody is a Simon Snow fan, but for Cath, being a fan is her life. Cath's sister has mostly grown away from fandom, but Cath just can't let go... Cath just wants to hang out with her twin sister and write fanfiction. But now that they're in college, her sister doesn't have time for her. And life keeps pulling Cath further and further out of her shell. For the first time ever, Cath has her own social circle. There's Nick, her handsome classmate who wants her to write short stories with him... And then Levi, who keeps showing up when she isn't looking for him... Actually...maybe Cath's circle is more of a triangle?"--Amazon.